The Use of Indonesian Folklores to Develop Young Learners’ Analytical and Critical Reasoning Skills - Yuli Christiana Yoedo; Ali Mustofa (Universitas Pendidikan Mandalika, 2022)
This study explored the way in which Elementary School teachers used Indonesian folklore in their English classes to help students improve their analytical and critical reasoning skills. Visual culture theory was employed to examine data from interviews through the use of pictures. Moreover, Kress’ (1991) social-constructionist method was applied to investigate the additional realities of folktales as a cultural reality. A descriptive qualitative research method was implemented. The data used were the five English teachers’ teaching strategies. The study revealed that the teachers’ final goal was for students to understand the moral message in the folklore. The teachers were innovative in their teaching materials and approach in their EFL classes by integrating illustrations and other visual media related to folklore in language teaching. Visual media was believed to help language development and vice versa. The strategies included the use of videos with English subtitles, reading texts, questions and examples from real life. The teachers’ efforts were aimed at sharpening students’ analytical reasoning skills. Students needed to answer questions that strengthened their critical reasoning skills, identifying inequities and providing feasible solutions. Teachers, who had a crucial role in maximizing the advantage of using folklore, needed to tailor the story’s discussion to the students’ level of understanding. The outcome of the study inferred that the use of English translations of Indonesian folktales in the classroom potentially affected students’ English language development.